The Alat Pendeteksi Kadar Gula Darah Menggunakan Teknik Non-Invasive Berbasis NodeMCU ESP8266 - Mulana, Nina; Darmawan, Budi; Suksmadana, I Made Budi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This project focuses on the development of a non-invasive blood glucose detection device using an IoT based system with NodeMCU ESP8266 as its microprocessor. The rising health issues related to diabetes call for regular blood sampling. This study utilizes diffuse reflectance spectroscopy, where light is scattered when interacting with human issue, enabling non-invasive measurement. By integrating a photodiode and high-brightness LEDs with the NodeMCU ESP8266 microcontroller, the device measure blood glucose levels through finger placement. The result are displayed on an LCD screen and send to a Telegram Bot. this system aims to provide a convenient and painless alternative for routine blood glucose monitoring, especially for individuals with diabetes. After the design and construction of the non-invasive blood glucose detection device, testing was conducted, yielding an error percentage of 2.38% and a measurement accuracy rate of 97.62% based on ten data collection from different individuals.